Answer:
A
Step-by-step explanation
You can divide 6x,9y and -15 by 3
6x/3=2x
9y/3=3y
-15/3=(-5)
Combine them to get the factored form of 6x+9y-15:
3(2x+3y-5)
The correct answer is 'Equation F can be written as 2d + 1 = 3d + 7'. In order to find the answer to a system of equations, the two equations must be set equal to each other. For instance, if we had the equations x = y + 1 and x = 3y - 1, we would set the two equations equal to one another to find the answer.
x = y + 1
x = 3y - 1
y + 1 = 3y - 1
1 = 2y - 1
2 = 2y
1 = y
x = y + 1
x = 1 + 1
<span>x = 2
We can use this to solve the set of equations above.
</span><span>2d + 1 = 3d + 7
</span>1 = d + 7
-6 = d
c = 2d + 1
c = 2(-6) + 1
c = -12 + 1
c = -11
Hope this helps!
Answer:
11.333 infinity
Step-by-step explanation:
when you divide 34 by 3 you then get 11.3 infinity which would also be a repeating decimal
Answer: diagonal
Step-by-step explanation: